2020
DOI: 10.1093/cdn/nzaa154
|View full text |Cite
|
Sign up to set email alerts
|

Examining Equitable Online Federal Food Assistance during the Severe Acute Respiratory Syndrome Coronavirus 2 (SARS-CoV-2): A Case Study in 2 Regions

Abstract: The United States Department of Agriculture Supplemental Nutrition Assistance Program (SNAP) provides food and financial assistance to food insecure individuals and families. In the midst of the SARS-CoV-2 pandemic, SNAP benefits evolved. Policy changes and federal legislation expanded SNAP eligibility, raised benefit levels, and introduced program waivers that enabled online ordering to reduce participants’ exposure to community-acquired SARS-CoV-2. Although rapid expansion of SNAP benefits in the online spac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 4 publications
0
9
0
Order By: Relevance
“…The growth predictions of online grocery shopping [ 2 , 36 ], in addition to the already existing online shopping options, has shed light on how the food environment as a whole is growing and evolving. Customers have even more ways to acquire food and, thus, research needs to keep pace with how customers are interacting with their food environment, and to make access to this type of shopping more equitable across geographic and socioeconomic differences [ 4 , 7 , 34 ]. There needs to be a concerted effort to understand and intervene within this food venue space in order to help consumers make healthful choices.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The growth predictions of online grocery shopping [ 2 , 36 ], in addition to the already existing online shopping options, has shed light on how the food environment as a whole is growing and evolving. Customers have even more ways to acquire food and, thus, research needs to keep pace with how customers are interacting with their food environment, and to make access to this type of shopping more equitable across geographic and socioeconomic differences [ 4 , 7 , 34 ]. There needs to be a concerted effort to understand and intervene within this food venue space in order to help consumers make healthful choices.…”
Section: Discussionmentioning
confidence: 99%
“…Yet, rural customers, and those participating in the supplemental nutrition assistance program (SNAP), still report barriers to online grocery ordering, including delivery fees, inconvenient pick-up times, and an overall lack of availability of online grocery services in their geographic area [ 3 , 4 , 5 ]. Recent evidence suggests a limited uptake of online grocery shopping, especially among rural populations, even when financial incentives are provided [ 6 , 7 ]. However, there are strong indicators that those who shop online spend less overall, purchase less sugary snacks and candies, and purchase more fruits and vegetables [ 8 , 9 , 10 , 11 , 12 , 13 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…14 As technology continues to advance and POS systems become more robust, the level and type of data shared with researchers is also expanding. 14 A recent scoping review found that the majority of programs operated with coupons, vouchers, or tokens, with only a few programs operating POS-driven methods. 12 Conversely, FD settings continue to grapple with implementation of advanced technology that allows for robust data due to barriers (e.g., no landline, cost of technology).…”
Section: Discussionmentioning
confidence: 99%
“…With respect to research, more work is needed to understand the most effective approaches to delivering nutrition information to SNAP participants in the online setting and how to best nudge these customers toward healthier purchases. 36 Further work could also explore how states can provide culturally and contextually relevant tips for how SNAP participants can best use online retailers to maximize nutritious choices. Finally, ongoing assessments of state communication about SNAP online, with a particular focus on health and nutrition information, would complement existing guidance such as the SNAP Online: A Review of State Government SNAP Websites 18 and provide important insights about changes in communication strategies.…”
Section: Implications For Research and Practicementioning
confidence: 99%